Efektivnost asimetrične konkurencije u telekomunikacijskom usluživanju - Bošnjak, Ivan (Promet - Traffic&Transportation, 2012)
Some relevant studies show that telecommunications and respective system of services (utilization) possess the characteristics of a natural monopoly, further confirmed by the established effects of the economic scale of 1.04-1.16. Nevertheless the effects of liberalization and privatization and introduction of competition in a number of countries are positive and filter through to even the level of local network and lines. Within this scope (from the aspect business administration of operations) the thesis has been developed that the possible efficient solution refers to an asymmetrical aspect of competition with competitors’ access permissions 011 the basis of concessions and compensations. Respective concept can find its justification in the case of a low level (smaller volumes) of telecommunications system development - the system of basic services - while for the telematic services an open competition is desirable.